Assessment of smartphone addiction and its relationship with health-promoting lifestyle profile and intuitive eating behavior: a cross-sectional study - Ding, Zhen; Pei, Qichuan; Fang, Tianle; Xiao, Lishun; Yin, Dehui; Sun, Zhiming (Frontiers in Psychiatry, 2025)
BackgroundSmartphones have become an essential part of daily life, but excessive use can lead to significant issues. This study assesses smartphone addiction among college students, examining its impact on dietary behaviors and health-promoting lifestyles. The aim is to provide a basis for targeted interventions.MethodsA cross-sectional study was conducted among 1,002 students at Xuzhou Medical University in 2025 using a convenience sampling. Data were collected via questionnaires and analyzed using SPSS 21.0. The study used the Smartphone Addiction Scale-Short Version (SAS-SV), the Health-Promoting Lifestyle Profile (HPLP-II), and the Intuitive Eating Scale-2 (IES-2). Statistical methods included normality tests, descriptive statistics, and mediation analysis.ResultsAmong the participants, medical students scored 34 (SAS), 74 (IES), and 134 (HPLP-II), while non-medical students scored 33.5 (SAS), 74 (IES), and 134 (HPLP-II). A negative correlation was observed between smartphone addiction and both intuitive eating (r = -0.174, p < 0.01) and health-promoting lifestyle (r = -0.074, p < 0.01). However, the effect sizes for these correlations are small, suggesting that, although statistically significant, the practical significance of these relationships may be limited. Intuitive eating mediated the relationship between smartphone addiction and health-promoting lifestyle (indirect effect = -0.1452, p < 0.001). Approximately 25.25% of participants reported feeling addicted to smartphones.ConclusionSmartphones have dual impacts on students’ eating behaviors and health. Excessive use is associated with disrupted eating patterns, while moderate use is associated with healthy behaviors that support well-being. It is crucial to educate students on balancing smartphone use with healthy habits is crucial. However, it is important to note that these findings, derived from a convenience sample at a single medical university, may not be fully generalizable to all college student populations. Future research with more diverse samples is needed to confirm these relationships.